2017
DOI: 10.1063/1.4997601
|View full text |Cite
|
Sign up to set email alerts
|

BInGaN alloys nearly lattice-matched to GaN for high-power high-efficiency visible LEDs

Abstract: InGaN-based visible LEDs find commercial applications for solid-state lighting and displays, but lattice mismatch limits the thickness of InGaN quantum wells that can be grown on GaN with high crystalline quality. Since narrower wells operate at a higher carrier density for a given current density, they increase the fraction of carriers lost to Auger recombination and lower the efficiency. The incorporation of boron, a smaller group-III element, into InGaN alloys is a promising method to eliminate the lattice … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…The quaternary BInGaN alloys are also predicted to maintain bandgaps similar to InGaN at a given indium concentration, meanwhile reducing the lattice mismatch to GaN. 9 This gives the opportunity to overcome the problem of efficiency drop at longer wavelengths in InGaN LEDs. Ab initio calculations predict zero heterointerface polarization for BGaN/BAlN and BAlN/BGaN heterojunctions with a certain B content, 10 which allows for the elimination of quantum-confined Stark effect present in GaN-based devices.…”
Section: Introductionmentioning
confidence: 99%
“…The quaternary BInGaN alloys are also predicted to maintain bandgaps similar to InGaN at a given indium concentration, meanwhile reducing the lattice mismatch to GaN. 9 This gives the opportunity to overcome the problem of efficiency drop at longer wavelengths in InGaN LEDs. Ab initio calculations predict zero heterointerface polarization for BGaN/BAlN and BAlN/BGaN heterojunctions with a certain B content, 10 which allows for the elimination of quantum-confined Stark effect present in GaN-based devices.…”
Section: Introductionmentioning
confidence: 99%
“…These quaternary alloys maintain an approximate lattice match to GaN while allowing for a band gap that is adjustable throughout the visible range. 9 Co-alloying has previously been demonstrated as a method to independently vary the lattice constant and band gap in other material systems. Chai et al found that the incorporation of Bi into In0.53Ga0.47As to form In0.53Ga0.47BixAs1-x increases the lattice constant and lowers the band gap for x up to 0.058.…”
Section: Introductionmentioning
confidence: 99%
“…We have also previously shown that co-alloying produces BInGaN alloys that lattice match GaN with reduced band gaps. 12) Applying Vegard's law to BAlGaN alloys and using our calculated lattice constants of GaN (3.1927Å), AlN (3.1183Å), and w-BN (2.5516Å), we estimate that alloys with a composition of approximately (B 0.116 Ga 0.884 ) x Al 1-x N (B-to-Ga ratio of approximately 1:7.62) are lattice matched to AlN.…”
mentioning
confidence: 86%
“…This behavior is the opposite of the trend seen in boron doping of InGaN alloys, in which the c lattice direction is more strongly affected by boron incorporation than the a lattice direction. 12) The exact cause of this behavior is unclear, but we speculate it could be due to anisotropic lattice distortions of the boron local bonding environments.…”
mentioning
confidence: 89%
See 1 more Smart Citation